Global burden of disease for colorectal cancer due to diet low in whole grains from 1990 to 2021 and its projections to 2050: analysis of the global burden of disease study 2021 - Yang, Mei; Huang, Gansheng; Jiang, Feng; Guo, Zaijin (Frontiers in Nutrition, 2025)
IntroductionColorectal cancer is a highly prevalent and significantly lethal digestive malignancy worldwide. This study aims to reveal the evolution of the disease burden of CRC associated with a low-grain diet from 1990 to 2021, to predict future trends, and to provide a scientific basis for differentiated prevention and control strategies.MethodsThe study integrated GBD 2021 data covering 204 countries and territories to assess the disease burden of CRC associated with a low-grain diet by the number of deaths, disability-adjusted life-years (DALYs), age-standardized mortality rates (ASMR), and Age-standardized DALYs rates (ASDR). Trends were quantified using Estimated Annual Percentage Change (EAPC) and disease burden was projected to 2050 using Bayesian Age-Period-Cohort (BAPC) modeling. Decomposition analyses explored the impact of population growth, aging, and epidemiologic changes on burden.ResultsBetween 1990 and 2021, the number of CRC deaths associated with a low proportion of whole grain diets worldwide increased by 82.94%, and disability adjusted life years increased by 70.3%. There is significant heterogeneity between regions: regions with high Social Population Index (SDI) have the highest decrease rate, while regions with low to medium SDI have the fastest increase rate. Age analysis shows that the disease burden is highest in the 50–85 age group, with males having a significantly higher risk than females. The BAPC model predicts that by 2050, global ASMR and ASDR will further decline, and decomposition analysis shows that population growth is the main reason for the increase in burden.ConclusionAge-standardized mortality rates and ASDR for CRC due to low whole grain diets declined globally between 1990 and 2021, but the absolute number of cases continues to increase. Low whole grain diet is an important modifiable factor in the disease burden of CRC, with significant age, sex, and regional heterogeneity in its impact. Bayesian BAPC model predictions showed a decreasing trend in ASMR and ASDR for colorectal cancer disease burden associated with low grain diets, but the absolute burden continued to increase due to increased aging. Decomposition analyses showed that population growth was the main cause of the increasing burden.